2016
DOI: 10.1002/crat.201500301
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical properties of pentaerythritol tetranitrate(PETN) single crystals from nano‐indentation: Depth dependent response at the nano meter scale

Abstract: The current work presents the results from an investigation of the mechanical behavior of single crystals of the energetic material pentaerythritol tetranitrate (PETN) using a nano‐indentation technique. The indentation tests have been performed on the maximum growth habit face (110) of the PETN, using a spherical, Berkovich and an anisometric (wedge‐shaped) tip. The load displacement curves along with analysis have been used to extract the mechanical properties and identify the anisotropic indentation modulus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 62 publications
0
6
0
Order By: Relevance
“…Other studies on PETN powder have shown similar trends with properties such as surface area coarsening, where newly synthesized PETN initially coarsens at a very high rate but the rates soon become much more gradual, if not completely stable [33,34]. [18], showing a dramatic depth dependence for elastic modulus. Their results showed that PETN appeared to be stiffer (i.e., higher modulus) at the surface, with a significantly decreasing stiffness as a function of depth (indenter penetration) into the material.…”
Section: Hardness and Modulus Measurementsmentioning
confidence: 53%
See 2 more Smart Citations
“…Other studies on PETN powder have shown similar trends with properties such as surface area coarsening, where newly synthesized PETN initially coarsens at a very high rate but the rates soon become much more gradual, if not completely stable [33,34]. [18], showing a dramatic depth dependence for elastic modulus. Their results showed that PETN appeared to be stiffer (i.e., higher modulus) at the surface, with a significantly decreasing stiffness as a function of depth (indenter penetration) into the material.…”
Section: Hardness and Modulus Measurementsmentioning
confidence: 53%
“…Load-depth data from several such indents per material were analyzed using the method described by Oliver and Pharr [22] to obtain elastic modulus and hardness values, averages for which are reported for each material in Table 3. Nanoindentation results for PETN were previously published by Zhai and McKenna [18], showing a dramatic depth dependence for elastic modulus. Their results showed that PETN appeared to be stiffer (i.e., higher modulus) at the surface, with a significantly decreasing stiffness as a function of depth (indenter penetration) into the material.…”
Section: Hardness and Modulus Measurementsmentioning
confidence: 76%
See 1 more Smart Citation
“…(b) is reprinted from ref , Copyright (2007), with permission from Springer Nature. (c) is reprinted from ref , Copyright (2010), and (e) is reprinted from ref , Copyright (2016), with permissions from John Wiley & Sons.…”
Section: Discussionmentioning
confidence: 99%
“…The understanding of mechanical deformation and fracture in molecular crystals remains less mature than in other classes of materials [7]. While indentation-based methods have proven valuable for investigating strength and elasticity [8][9][10][11][12][13][14][15][16][17], such approaches provide less insight into constitutive stress-strain response, fracture, and extrinsic length scale-or shape-dependent changes in deformation behavior. Indentation fracture methods [18] have been utilized successfully in some cases, but high degrees of anisotropy generally lead to difficulties in applying these approaches to molecular crystals [16].…”
Section: Introductionmentioning
confidence: 99%